Faktor-Faktor yang Mempengaruhi Kesehatan Mental pada Remaja: Factors Affecting Mental Health in Adolesents - Fetty Rahmawaty; Ribka Pebriani Silalahi; Berthiana T; Barto Mansyah (Jurnal Surya Medika (JSM), 2022)
Adolescence is a period of transition from childhood to adulthood. During adolescence, there are many changes, such as physical, biological, and emotional changes. Many teenagers only focus on their physical health. In addition to physical health, mental health is also important to pay attention to because mental health affects the way a person thinks, feels, and acts in his daily life. Someone who has good mental health will be able to develop their potential well. To find out the factors that influence mental health in adolescents. Two article search engines are used, namely Google Scholar and Neliti, with a vulnerability of 2016-2021. There are 3 types of research identified namely quantitative and cross-sectional research. The results of the literature review research on the 3 journals showed that the results in journal 1 showed that authoritarian and permissive parenting styles applied by parents affected adolescents' mental health, in journal 2 showed that gratitude affected adolescent mental health. In the 3rd journal, it was shown that the type of Gender affects mental health in adolescents. Factors that affect mental health in adolescents include parenting style adopted by parents, gratitude, and gender.